Sarah E. Rollens, Eric M. Vanden Eykel, and Meredith J. C. Warren, Eds. Judeophobia and the New Testament: Texts and Contexts - Schwartz, Ethan (Studies in Christian-Jewish Relations, 2025)
No abstract is available.